1997
DOI: 10.1021/jf960121b
|View full text |Cite
|
Sign up to set email alerts
|

Determining Ten Synthetic Pyrethroids in Lettuce and Ground Meat by Using Ion-Trap Mass Spectrometry and Electron-Capture Gas Chromatography

Abstract: Conventional extraction procedures with acetonitrile were compared with supercritical fluid extraction (SFE) with CO2 for determining 10 pyrethroids in fortified lettuce and meat samples. Because SFE utilized a minimal cleanup procedure, nonvolatiles may accumulate on the capillary column in both the gas chromatography-ion trap mass spectrometry (GC-ITMS) and electron capture (EC) detection modes shortening the lifetime of the columns after multiple injections. The GC-ITMS method proved satisfactory for analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…Direct methods for determination of fenvalerate are mainly based on gas chromatography (GC) [1,2,3,4], high-performance liquid chromatography (HPLC) [5], or thin-layer chromatography (TLC) [6,7]. Argauer et al [8]. developed ion-trap mass spectrometry and electron-capture gas chromatography methods for determination of ten pyrethroids in fortified lettuce and meat samples.…”
Section: Introductionmentioning
confidence: 99%
“…Direct methods for determination of fenvalerate are mainly based on gas chromatography (GC) [1,2,3,4], high-performance liquid chromatography (HPLC) [5], or thin-layer chromatography (TLC) [6,7]. Argauer et al [8]. developed ion-trap mass spectrometry and electron-capture gas chromatography methods for determination of ten pyrethroids in fortified lettuce and meat samples.…”
Section: Introductionmentioning
confidence: 99%
“…This procedure consists in grinding chopped samples or extracted fats several times at high speed in selected organic solvents. This technical procedure has been applied to meat and meat products [3,7,11,12,15,33,35,42,43,[68][69][70], animal fat [14,27,29,30,36], offal [25,29,41], eggs [44][45][46][47]71] and fish [31,36] for extracting different kinds of pesticides. Similarly, liquid-liquid extraction (LLE) is still the preferred method for extracting pesticide residues from liquid milk [10,25,29,30,35,55,57,69,70,72,73].…”
Section: Extraction Methodsmentioning
confidence: 99%
“…While pesticide compounds are mostly stored in the fat and muscle of animals, they can also reach other compartments such as the brain, liver and lungs [26]. Consequently, these chemical residues have been studied in the meat [14,27] and adipose tissue [14,28] of various species such as dairy cattle [29], beef cattle [3,12,15,[30][31][32][33][34], pigs [25,26,31,[35][36][37], sheep [34,37,38], rabbits [7], and camel [34]. Some papers have also reported on pesticide determination in offal [1,[39][40][41] and in food containing meat products, such as infant [42] and processed [6,11,43] foods.…”
Section: Meat and Meat Productsmentioning
confidence: 99%
“…Fat was mixed with deactivated Florisil ® and packed into a disposable column which was then stacked tandem with a C18 SPE column and eluted with ACN. Argauer et al developed a method to isolate ten pyrethroids from ground meat using SF-CO2 [382]. Rissato et al reported a SFE method that combined extraction and Florisil ® clean up of pyrethroids residues from honey samples [383].…”
Section: Pyrethroidsmentioning
confidence: 99%